2019
DOI: 10.1101/gad.321174.118
|View full text |Cite
|
Sign up to set email alerts
|

Dppa2 and Dppa4 directly regulate the Dux-driven zygotic transcriptional program

Abstract: The molecular regulation of zygotic genome activation (ZGA) in mammals remains an exciting area of research. Primed mouse embryonic stem cells contain a rare subset of "2C-like" cells that are epigenetically and transcriptionally similar to the two-cell embryo and thus represent an in vitro approximation for studying ZGA transcription regulation. Recently, the transcription factor Dux, expressed in the minor wave of ZGA, was described to activate many downstream ZGA transcripts. However, it remains unknown wha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
209
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(232 citation statements)
references
References 57 publications
(108 reference statements)
22
209
0
1
Order By: Relevance
“…Two-cell-like cells emerge from cells that express the transcription factor Zscan4 (Zscan4 + cells) [16], which are yet another subpopulation of ESC cultures constituting approximately 5% of the cell population [17,18]. Early-embryonic-like cells (Zscan4 + and 2-cell-like cells) can be induced in culture through the modulation of specific chromatin pathways, including the chromatin assembly factor 1 (CAF-1) [15] and the non-canonical polycomb repressive complex PRC1.6 [16,19], as well as the transcription factors Dux and Dppa2/4 [12,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Two-cell-like cells emerge from cells that express the transcription factor Zscan4 (Zscan4 + cells) [16], which are yet another subpopulation of ESC cultures constituting approximately 5% of the cell population [17,18]. Early-embryonic-like cells (Zscan4 + and 2-cell-like cells) can be induced in culture through the modulation of specific chromatin pathways, including the chromatin assembly factor 1 (CAF-1) [15] and the non-canonical polycomb repressive complex PRC1.6 [16,19], as well as the transcription factors Dux and Dppa2/4 [12,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that a ZGA-like state can be mimicked in mouse ESCs (Macfarlan et al 2012;Zalzman et al 2010;Bošković et al 2014;Ishiuchi et al 2015;Akiyama et al 2015;Eckersley-Maslin et al 2016;Rodriguez-Terrones et al 2018). Consequently, these cells represent an ideal system for in vitro screening and have been previously used to identify regulators of ZGA (Fu et al 2019;Yan et al 2019;Eckersley-Maslin et al 2019;Rodriguez-Terrones et al 2018). While most of these studies probing ZGA regulators in ESCs have focused on repressors (Fu et al 2019;Rodriguez-Terrones et al 2018), positive inducers of ZGA have thus far not been interrogated in a systematic manner.…”
Section: Introductionmentioning
confidence: 99%
“…While most of these studies probing ZGA regulators in ESCs have focused on repressors (Fu et al 2019;Rodriguez-Terrones et al 2018), positive inducers of ZGA have thus far not been interrogated in a systematic manner. Such regulators are more relevant given the transcriptionally inactive state prior to ZGA and could be identified in ESCs by assessing the transcriptional changes triggered downstream of their overexpression (Eckersley-Maslin et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…RNA sequencing of these iPSC clones as well as wild-type ESCs was analyzed one month after miR-203 induction ( Fig 1B) and surprisingly revealed that miiPSCs cells were transcriptionally closer to ESCs than Dox-treated wild-type iPSCs both at the genomewide level ( Fig 1C) and when considering a pluripotency-associated signature defined previously 15 (Fig EV1D). In addition, almost every transcript included in a 282-gene signature of 2C blastomeres 16 was induced by miR-203 and sustained during ten days after Dox withdrawal ( Fig 1D and EV1E), including genes such as Zscan4c previously related to the zygotic transcriptional program 17 . An additional comparison of the expression profiles in miiPSCs versus un-induced iPSCs at day 30 after doxycycline withdrawal suggested higher expression of genes related to tissue morphogenesis and embryonic development in those clones in which miR-203 had been transiently induced ( Fig 1B, EV1F and Supplementary Table 1).…”
Section: Mir-203 Improves the Differentiation Potency Of Pscsmentioning
confidence: 95%